Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan Dan Ukuran Perusahaan Terhadap Manajemen Laba - Tutik Avrinia Wulansari (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2019)
Effect of Tax Planning, Deferred Tax Expense And Size Company on Profit Management (Case study onfood and beverage industry financial reports listed on the IDX).The purpose of this study is to prove whether the hypothesis is arranged based on background and previous research is accepted or not. This type of research is quantitative descriptive. The population in this study is the consumer goods industry (food and beverage) listed on the Indonesia Stock Exchange for the period 2016-2018. The samples in this study were 10 companies. The sampling technique in this study used a purposive sampling technique. The research data are secondary data in the form of food and beverage industry financial reports listed on the IDX. Data is downloaded through www.idx.co.id. The hypothesis test results of this research are profit management can be influenced by tax planning variables, deferred tax expense, and company size and the remaining 74.9% can be influenced by other variables.